Enhancing UI/UX of The Smart Village System Website Using User-Centered Design Methods - Alek Wijaya; Fauzan Azhiman (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
The Smart Village System is a platform specifically designed to help publicize village potential. Of course, it is very important to test UI/UX on sidespin websites which are still very far from perfect, so it becomes a question of whether the UI/UX sidespin is in line with the expectations of the community as the target user. This study intends to design UI/UX on sidespin websites by utilizing the UCD method which aims to improve interface quality, efficiency, and productivity as well as community satisfaction. The UI/UX design on this sidespin website uses the UCD method because several stages involve establishing a relationship and interaction between users. 5 people are willing to become User Personas who can provide input on user satisfaction which will be evaluated using a Heuristic Evaluation which will be combined with Survey Ratings. The results of this study state that all aspects of the satisfaction level of the User Persona are in the satisfied category. Recommendations were found to be developed by the Smart Village System Team, among others, in terms of the principles of Heuristic Evaluation 4, 5, and 6. Consistency and Standards have restructured sentences and are consistent from one page to another. Error Prevention has added many features to the sidespin and finally, Recognition rather than recall has implemented local and rural nuances on the page sidespin.